UJI AKTIVITAS ANTIBAKTERI FRAKSI n-HEKSANA DAUN KESUM (Polygonum minus Huds.) TERHADAP Salmonella typhi - ., Esti Nur Ekasari (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background: Kesum (Polygonum minus Huds.) is an endemic plant of West Kalimantan. This plant was used by people to treat gastrointestinaldisorders of typhoid fever. Typhoid fever was caused by Salmonella typhi.Objective: This research aimed to investigate the antibacterial activity of nhexanefraction of kesum leaf against the growth of Salmonella typhi, thecontent of secondary metabolite compounds, and the effectiveconcentration from n-hexane fraction of kesum leaf to inhibit the growth ofSalmonella typhi. Methodology: Kesum leaf(ves) were extracted bymaceration using methanol. The extract was fractioned using n-hexane. Its chemical compounds were determined by phytochemical screening. Thefraction was tested its antibacterial activity using Kirby-Bauer Disc Diffusion.Ciprofloxacin 5 Âµg/disk was used as positive control and tween 20 0,8% was used as negative control. Result: Based on phytochemical screening, nhexane fraction of kesum leaf(ves) contained steroid. N-hexane fraction of kesum leaf(ves) showed no antibacterial activity against the growth ofSalmonella typhi. Conclusion: N-hexane fraction of kesum leaf(ves) hadno antibacterial activity against the growth of Salmonella typhi. Â Keywords: Antibacterial, n-hexane fraction of kesum leaf, Salmonella typhi1) Medical Education Study Program, Faculty of Medicine, Universitas Tanjungpura, Pontianak, West Kalimantan2) Chemical Study Program, Faculty of Mathematics and Natural Science, Universitas of Tanjungpura, Pontianak, West Kalimantan3) Medical Education Study Program, Faculty of Medicine, Universitas Tanjungpura, Pontianak, West Kalimantan